A clinical case of a rare complication of infectious mononucleosis associated with the Epstein-Barr virus - I. A. Otmakhova; O. L. Sobolevskaya; A. S. Belousova; T. M. Kharitonova; V. D. Shpilevsky (Журнал инфектологии, 2024)
This clinical case describes a rare clinical complication of infectious mononucleosis associated with Epstein-Barr virus in a 19-year-old patient. The current literature sources; medical history; examination data and discharge epicrisis of the patient are analyzed. Rupture of the spleen is an extremely rare complication that develops in 1% of patients against the background of infection. At the same time; the diagnosis of the complication is not very difficult – it is necessary to conduct ultrasound of the abdominal organs in dynamics in the event of a rupture clinic (critical days of the disease are especially important – 10-20 days). But due to its rarity; many clinicians forget about the possibility of developing this complication. The main purpose of the work is to attract attention and alertness to the potentially fatal complication of infectious mononucleosis.